2021
DOI: 10.1039/d1dt02989d
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor and hydrogen gas diffusion barrier characteristics of Al2O3–alucone multi-layer structures for flexible OLED display applications

Abstract: Organic light emitting diodes (OLED) and amorphous oxide semiconductors (AOSs), which are very important technologies in high performance flexible displays, have issues related to degradation due to diffusion of water...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The most important benefit of [Al(NiPr2)2(DMP)] over the TMA is the highly competitive GPC value of 4.2 Å/cycle at 95 o C. Interestingly, this value is higher compared to the value of 3.4 Å/cycle reported for an Al-HQ layer grown from TMA on top of an Al2O3 layer at 100 °C. 69 To verify the self-limiting growth mode expected for an ideal ALD/MLD process, we confirmed that the GPC value saturated when the precursor pulse lengths of [Al(NiPr2)2(DMP)] and HQ were individually increased; this data are shown in Figure 1(a). As can be seen, the growth rate is only weakly dependent on the precursor pulse lengths; a small increasing trend is seen for [Al(NiPr2)2(DMP)] up to 7 s, and for HQ up to 8 s. Interestingly, the former pulse length is exactly what was found for the same [Al(NiPr2)2(DMP)] precursor in the water assisted thermal ALD process for the deposition of Al2O3 films.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The most important benefit of [Al(NiPr2)2(DMP)] over the TMA is the highly competitive GPC value of 4.2 Å/cycle at 95 o C. Interestingly, this value is higher compared to the value of 3.4 Å/cycle reported for an Al-HQ layer grown from TMA on top of an Al2O3 layer at 100 °C. 69 To verify the self-limiting growth mode expected for an ideal ALD/MLD process, we confirmed that the GPC value saturated when the precursor pulse lengths of [Al(NiPr2)2(DMP)] and HQ were individually increased; this data are shown in Figure 1(a). As can be seen, the growth rate is only weakly dependent on the precursor pulse lengths; a small increasing trend is seen for [Al(NiPr2)2(DMP)] up to 7 s, and for HQ up to 8 s. Interestingly, the former pulse length is exactly what was found for the same [Al(NiPr2)2(DMP)] precursor in the water assisted thermal ALD process for the deposition of Al2O3 films.…”
Section: Resultssupporting
confidence: 52%
“…Interestingly, this value is higher compared to the value of 3.4 Å / cycle reported for an Al-HQ layer grown from TMA on top of an Al 2 O 3 layer at 100 °C. 69 To verify the self-limiting growth mode expected for an ideal ALD/MLD process, we confirmed that the GPC value saturated when the precursor pulse lengths of [Al(NiPr 2 ) 2 (DMP)] and HQ were individually increased; this data is shown in Fig. 1(a).…”
Section: Papersupporting
confidence: 57%
See 1 more Smart Citation
“…Metal-oxide-based hybrid thin film multilayers have been fabricated by sequential atomic layer deposition (ALD) and molecular layer deposition (MLD). Such nanolaminates exhibit unusual property combinations different from that of the constituent materials, e.g., high electrical and low thermal conductivities, , and mechanical flexibility. , However, very little is known about the effects of the MNL structure and chemistry on the nano/micro-scale structure, morphology, and phase stability of inorganic nanolayers, as well as the inorganic/MNL interfaces …”
Section: Introductionmentioning
confidence: 99%
“…Such nanolaminates exhibit unusual property combinations different from that of the constituent materials, e.g., high electrical 12 and low thermal conductivities, 14,15 and mechanical flexibility. 16,17 However, very little is known about the effects of the MNL structure and chemistry on the nano/micro-scale structure, morphology, and phase stability of inorganic nanolayers, as well as the inorganic/ MNL interfaces. 18 Here, we report the synthesis of titania/organophosphate-MNL multilayers (see Scheme in Figure 1) and describe MNLinduced decreases in the titania nanolayer growth rate, suppression of anatase nanocrystal formation, and increases in surface roughness.…”
Section: Introductionmentioning
confidence: 99%